Accuracy of lung and diaphragm ultrasound in predicting infant weaning outcomes: a systematic review and meta-analysis - Gao, Yang; Yin, Hong; Wang, Mei-Huan; Gao, Yue-Hua (Frontiers in Pediatrics, 2023)
Background Although lung and diaphragm ultrasound are valuable tools for predicting weaning results in adults with MV, their relevance in children is debatable. The goal of this meta-analysis was to determine the predictive value of lung and diaphragm ultrasound in newborn weaning outcomes. Methods For eligible studies, the databases MEDLINE, Web of Science, Cochrane Library, PubMed, and Embase were thoroughly searched. The Quality Assessment of Diagnostic Accuracy Studies (QUADAS−2) method was used to evaluate the study's quality. Results were gathered for sensitivity, specificity, diagnostic odds ratio (DOR), and the area under the curve of summary receiver operating characteristic curves (AUSROC). To investigate the causes of heterogeneity, subgroup analyses and meta-regression were conducted. Results A total of 11 studies were suitable for inclusion in the meta-analysis, which included 828 patients. The pooled sensitivity and specificity of lung ultrasound (LUS) were 0.88 (95%CI, 0.85–0.90) and 0.81 (95%CI, 0.75–0.87), respectively. The DOR for diaphragmatic excursion (DE) is 13.17 (95%CI, 5.65–30.71). The AUSROC for diaphragm thickening fraction (DTF) is 0.86 (95%CI, 0.82–0.89). The most sensitive and specific method is LUS. The DE and DTF were the key areas where study heterogeneity was evident. Conclusions Lung ultrasonography is an extremely accurate method for predicting weaning results in MV infants. DTF outperforms DE in terms of diaphragm ultrasound predictive power.